The Role of Women in Regional Touris Development (Study Literature Tourism in Indonesia) - Mukarromah Mukarromah; Pawito Pawito; Albert Muhammad Isrun Naini (English Language and Literature International Conference (ELLiC) Proceedings, 2023)
The development of tourism in Indonesia is progressing so fast and has increased the welfare of the community. This article discusses the role of women in supporting the development of sustainable tourism in Indonesia. In facing the challenges of the era of disruption in building leading tourism destinations, a strong figure is needed, especially for women. Until now, not many studies have been conducted on the role of women in the halal tourism industry, so this article will explain in more detail the role of women in Indonesia. This study aims to see how the role of women in digital marketing, especially halal tourism in Indonesia. The method used in this study is a literature study collected for the last 10 years. The data used in this study are secondary data from national and international scientific papers. The databases used are Google Scholar, Pubmed, Science Direct and Scopus.. After all the data has been collected, then a systematic review and comparison of the data found are carried out. Based on the results of research conducted by researchers on the role of women in building local tourism through various activities by preserving local culture in the form of local customs, the role of women can be the management of tourist facilities such as homestays, food, and drink, marketing souvenirs and women in managing tourism organizations. Women have the ability to help develop tourism in Indonesia so that it is growing.